시간적 추이에 따른 19세 이상 한국 성인 암환자의 자살생각 관련요인 -국민건강영양조사 (2009, 2017) - 성지숙(Ji-Suk Seong) (한국컴퓨터정보학회논문지, 2020)
본 연구는 국민건강영양조사의 자료를 이차분석하여 시간적 추이에 따른 19세 이상 한국 성인암환자의 자살생각 관련 요인을 파악하여 암환자 관리의 기초자료를 제공하기 위해 시도되었다. 자료는 IBM SPSS WIN 22.0 program을 이용하여 2009년, 2017년 2개년도 연구대상자의 인구사회학적 특성, 건강관련 특성, 정신관련 특성을 분석하기 위해 복합표본 빈도분석, 복합표본 교차분석, 복합표본 다중 로지스틱 회귀분석을 이용하여 분석하였다. 연구결과 암환자 자살생각 관련요인은 2009년 활동제한, 우울증상 경험으로 나타났고(Negelkerke R 2 =.384) 2017년 연령, 결혼상태, 활동제한, 우울증상 경험으로 나타났다(Negelkerke R 2=.525). 본 연구는 시간적 추이에 따른 암환자자살생각 관련요인을 파악하여 관련요인의 변화를 확인했다는 점에서 의의가 있으며, 암환자의자살을 예방할 수 있는 중재 프로그램의 개발 및 적용이 필요하다. In this paper, we propose the basic data for cancer patient management by secondary analysis of data from the National Health and Nutrition Survey(KNHANES) to identify factors related to suicidal thinking of cancer patients over 19 years of age in Korean adults lapse of time. The data were analyzed using the IBM SPSS WIN 22.0 program in order to analyze the demographic, health, and mental characteristics of the subjects in 2009 and 2017. It was analyzed using logistic regression analysis. As a result of the study, the factors related to suicidal thinking in cancer patients were activity restriction and experience of depression in 2009(Negelkerke R 2 =.384), and age, marital status, activity restriction, and experience of depression in 2017(Negelkerke R 2=.525). This study is meaningful in that the factors related to suicidal thoughts in cancer patients were identified according to the lapse of time, and the changes in the related factors were confirmed. Development and application of an intervention program to prevent suicide in cancer patients are necessary. KCI Citation Count: 0